The concrete other in the constitution of ethical subjectivity: Enrique Dussel, discourse ethics and communitarianism - Roldán, David A. (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The constitution of ethical subjectivity and alterity was not a theoretical problem of Antiquity, but rather of Modernity. In Classic Modernity the other appears as an ethical problem (not epistemological) and with the «School of Suspicion» the problem of the other and the constitution of ethical subjectivity take a central role. Enrique Dussel, under the influence of Heidegger and Levinas, develops a theory of the constitution of ethical subjectivity starting with the Concrete Other. This theory is constructed by the critical mediation of two main schools: Discourse Ethics (Apel, Habermas) and Communitarianism (McIntyre, Taylor). This article explores Dussel’s critical use of both schools. From Discourse Ethics he assimilates universality, and from Communitarianism he assimilates the search for an «ethic of contents». He critiques the formalism of Discourse Ethics, and the tendency towards relativism in Communitarianism.
Keywords: other; ethics; Dussel